Clinical observation of a patient with asthenic syndrome in the post-COVID-19 period - V. A. Sergeeva; K. V. Gogol; M. A. Kutina; I. E. Tyurina (Лечащий Врач, 2023)
Background. Currently, clinicians are facing a large number of patients who have passed a new coronavirus infection. Most of them have various manifestations of post-COVID-19 syndrome, among which numerous neurological and cardiovascular clinical symptoms are most often recorded. For example, fatigue (asthenia) according some authors its frequency can reach 70 %. Nonspecific manifestations of post-COVID-19 syndrome can mask the symptom complex of paraneoplastic syndrome, the prognosis of which is noticeably more serious. Paraneoplastic syndrome is a group of various clinical manifestations from various organ systems in patients with malignant neoplasms, not associated with the primary tumor focus or its metastasis. In most cases, the cause of paraneoplastic syndrome is the activation of tissue-specific autoimmunity, which is the result of an immune response against cancer. Clinical manifestations can be both neurological, endocrine, gastrointestinal, skin, and nonspecific symptoms, the frequency of which, according to recent data, can reach 10-18.5 %. The interaction of a new coronavirus infection and oncopathology is an urgent problem, while data in open sources are scarce. In most cases, a severe course of the infectious process, an increase in the duration of hospitalization, a worse prognosis for recovery and an increase in the frequency of deaths among such patients are reported.   Results. The article presents a clinical observation of a patient with a tumor lesion of the bladder with history of COVID-19 four months before the diagnosis of oncopathology. Of interest is the diagnostic search for the disease in conditions of minimal symptoms from the affected organ. Given the active examination of patients who have undergone COVID-19, despite the blurred clinical picture and the presence of non-specific clinical manifestations, many of them may suffer from oncological diseases, due to the negative trigger effect of SARS-CoV-2 on the tumor process.